Oxodegradable Polyethylene Biodegradation Using Lactobacillus casei - Filayani, Muhammad Iqbal; Pradana, Muhammad Riszky Wahyu; Izzah, Annisa Salsabila Zahrotul; Salsabila, Bilqis Fatimatus (El-Hayah:Jurnal Biologi, 2024)
The biodegradation of oxodegradable polyethylene has traditionally been carried out using pure strains of polyethylene-degrading agents. Research on polyethylene biodegradation is using other microbes than pure strains still scarce. This study utilized lactic acid bacteria, specifically Lactobacillus casei, to know the capability of Lactobacillus casei to degrade polyethylene. The results indicate that Lactobacillus casei can degrade polyethylene plastic. Polyethylene plastic biodegrades by 27.92% over 28 days without preheating. The optimal temperature and pH for the process are 26°C and pH 5, respectively. On the other hand, the preheated polyethylene plastic performed at 9.65% biodegradation over 28 days, with an optimum temperature of 28°C and an optimum pH of 5.6.  Key words: Biodegradation, percentage, oxodegradable,  polyethylene